One-pot synthesis of antimony oxide and bismuth oxide nanocomposites for the selective electrochemical determination of the anticancer drug methotrexate in biomedical samples. Issue 2 (15th January 2022) - Yamuna, Annamalai; Chen, Tse-Wei; Chen, Shen-Ming; Yu, Ming-Chin; Yu, Jaysan
Abstract: Methotrexate (MTRX) is an anticancer drug that is also used for several chronic illnesses; however, a high dosage of MTRX can cause adverse effects, so it is necessary to monitor the MTRX level in blood and urine samples. This work reports the electrochemical determination of MTRX based on Sb2 O3 and Bi2 O3 composite material (Sb2 O3 @Bi2 O3 )modified electrodes. The one-pot sonohydrolysis synthesis method is employed for the preparation of the Sb2 O3 @Bi2 O3 composite, which reveals high crystallinity with mixed phases of monoclinic Bi2 O3 and cubic Sb2 O3 . Furthermore, the phases are identified by XRD, Raman spectroscopy, XPS, and HRTEM analysis. This composite reveals nanoneedle and nanocube morphologies. The Sb2 O3 @Bi2 O3 modified GCE shows excellent electrochemical activity for the detection of the anticancer drug methotrexate (MTRX). The activity is compared with the individual Sb2 O3 and Bi2 O3 compounds. Sb2 O3 @Bi2 O3 /GCE shows good electroanalytical characteristics in chronoamperometric analysis. Sb2 O3 @Bi2 O3 /GCE exhibits a linear range of approximately 0.01 μM to 174.6 μM, a sensitivity of 1.46 μA cm -2 μM -1, and an LOD of 2.9 nM. Moreover, Sb2 O3 @Bi2 O3 /GCE delivered high selectivity among highly interfering compounds in blood and urine samples.